Frontier horizon - Sherman, George, 1908-1991; Wayne, John, 1907-1979; Burbridge, Betty; Ward, Luci, 1907-1969; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Pictures, 1939)
The Three Mesquiteers help the ranchers in New Hope Valley against a group of crooked politicians who want to build a dam for their own profit.
Originally produced in the United States as a motion picture in 1939.
Based on characters created by William Colt MacDonald.
John Wayne, Ray Corrigan, Raymond Hatton.
Cinematographer, Reggie Lanning; editor, Tony Martinelli ; music, William Lava.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Dams -- West (U.S.) -- Drama; Eminent domain -- West (U.S.) -- Drama; Water rights -- Corrupt practices -- West (U.S.) -- Drama; Real estate development -- Corrupt practices -- West (U.S.) -- Drama; Western films; Feature films; Fiction films; Internet videos; Streaming video